Analisis Faktor Pendorong Bagi Siswa untuk Masuk Seminari Menengah Mario John Boen-Pangkalpinang - Laurensius Dihe Sanga (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study aims to analyze the influence of personal motivation, popularity, and parental will on the decision of seminarians at Mario John Boen Minor Seminary in responding to the call to become priests. Through surveys and in-depth interviews, it was found that 86.0% of seminarians decided to become priests based on pure personal motivation, driven by a commitment to serve the people of God. Meanwhile, 12.0% of seminarians indicated that their decision to become a priest was influenced by the will of their parents and parish priests. Additionally, 1.0% of seminarians cited pursuing self-popularity and high curiosity as their reasons for the decision. These results indicate that personal motivation is the dominant factor in the seminarians' decision-making process, while the influence of popularity and parental will is relatively smaller. This study recommends strengthening spiritual formation programs at the seminary to continue supporting and reinforcing the seminarians' personal motivation so that they may pursue their priestly vocation with full commitment and integrity.